Life Cycle Assessment of bioenergy production from mountainous grasslands invaded by lupine (Lupinus polyphyllus Lindl.). (1st December 2020) - Joseph, Ben; Hensgen, Frank; Wachendorf, Michael
Abstract: Mountainous grasslands are typically important habitats both for fauna and flora but increasingly suffer from invasions by neophytes (i.e. Lupinus polyphyllus Lindl.) in most German low mountain areas, which eventually threatens species richness. Regular defoliation is required to eliminate the invasion, however, at present options to handle the harvested biomass are limited. Integrated generation of solid fuel and biogas from biomass (IFBB) and anaerobic digestion (AD) are two possible options to utilise the biomass and convert it into energy. There is substantial environmental impact associated with the energy and resource usage during conversion of the biomass into fuel and during usage of fuels and co-products obtained. This study examines IFBB and AD to identify the best option in terms of environmental impacts and primary energy usage, also looking at alternatives for process parameters along the life cycle that would reduce environmental impacts. It was found that IFBB was a better option compared to AD, as it had higher environmental and primary energy savings across all grassland sites. Higher energy conversion efficiency of IFBB resulted in higher greenhouse gas (GHG) and energy savings, even though the energy usage for the processing steps were higher compared to AD. Biomass yield was positively related to the savings, providing better GHG and energy savings for grasslands containing invasive species. There were no savings in terms of acidification (AP) and eutrophication potential (EP) for both IFBB and AD, however AP and EP was lower using IFBB compared to AD. Hence, biomass originating from mountainous grasslands with lupine invasion could be effectively utilised with IFBB, as this option had lower environmental impacts and higher energy savings compared to AD. Biomass from non-invaded grasslands could also be converted effectively using IFBB, hence IFBB could be used to utilise the harvested biomass in the situation where the invasion is eliminated. Highlights: Biomass was harvested to eliminate invasive species ( L. polyphyllus) . Harvested biomass with limited alternative uses was processed into fuel. IFBB and AD were used to process the biomass and they were compared in terms of environmental benefits. Environmental benefits were higher using IFBB compared to AD.